Isolation of Terpenes and Coumarin from the Stem Bark of Jatropha pandurifolia (Andr.) - Zohora, F.T.; Sarkar, P.; Tareq, F.S.; Islam, F.; Hasan, C.M.; Ahsan, M. (Asian Journal of Chemistry, 2012)
A total of seven compounds were isolated from the methanolic extract of the stem bark of Jatropha pandurifolia Andr. Their structures were identified as 3-O-acetylaleuritolic acid (1), jatropholone A (2), jatropholone B (3), 2a-hydroxyjatropholone (4), 2b- ydroxyljatropholone (5), scopoletin (6) and aleuritolic acid 3-p-hydroxycinnamate (7) by spectroscopic studies including 1H NMR analyses as well as by comparison with published data. Among them, compound (7) was the first occurrence from the genus of the Jatropha of Euphorbiaceae family and compound (1) and (6) were isolated for the first time from this plant.